2018
DOI: 10.1016/j.contraception.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Not seeking yet trying long-acting reversible contraception: a 24-month randomized trial on continuation, unintended pregnancy and satisfaction

Abstract: Even women who do not necessarily view LARC as a first choice may have a highly satisfying experience and avoid unintended pregnancy if they try it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
4
11
0
1
Order By: Relevance
“…This supports a qualitative study of adolescent current and former IUD users that found no difference in stated reasons for choosing the method between those who had continued versus those who had discontinued use [24]. In addition, in a study where some women seeking short-acting contraceptives were willing to be randomized to LARC method initiation, Hubacher et al found that negative baseline attitudes toward LARC among those randomized to it were not associated with discontinuation by 24 months of use [15].…”
Section: Discussionmentioning
confidence: 56%
“…This supports a qualitative study of adolescent current and former IUD users that found no difference in stated reasons for choosing the method between those who had continued versus those who had discontinued use [24]. In addition, in a study where some women seeking short-acting contraceptives were willing to be randomized to LARC method initiation, Hubacher et al found that negative baseline attitudes toward LARC among those randomized to it were not associated with discontinuation by 24 months of use [15].…”
Section: Discussionmentioning
confidence: 56%
“…Diaphragms have a moderate failure rate (12%/year) whereas hormonal methods that rely on correct and consistent use have failure rates of between 5% and 8% per year. LARC clearly provides the best protection against pregnancy with failure rate <1% per year and satisfaction with the most effective LARC methods can be high even for women whose initial preference is for a short‐acting method …”
Section: Methodsmentioning
confidence: 99%
“…The importance of long-acting reversible contraception (LARC; implants, intrauterine devices [IUDs] and the levonorgestrel-releasing intrauterine system [LNG-IUS]) in reducing the rate of unwanted pregnancy and abortion has recently become clear [6][7][8][9]. Better knowledge about contraception may help to promote LARC use among those most susceptible to unwanted pregnancies.…”
Section: Introductionmentioning
confidence: 99%